A Path Analysis of Sustaining Small Scale Fishing Industry in Indonesia - Dedy Putra Wahyudi; Eko Sri Wiyono; Budy Wiryawan; Iin Solihin (International Journal of Agriculture System, 2014)
The over exploitation of the international fishing activities does affect the sustainability of the local small-scale fishing industry. The small scale fishing industry sectors especially economic, social, ecological, and governance in Indonesia has not been well managed. The objective of this paper is therefore to analyze the causal relationships between the four variables using a path analysis technique. The results of this analysis showed that the economic factor has the largest effect on the small-scale fisheries system. Future studies should emphasized more on the economic variable to sustain the local fishing industry in Indonesia.